The Pathoanatomy of Posterolateral Corner Ligamentous Disruption in Multiligament Knee Injuries Is Predictive of Peroneal Nerve Injury. Issue 14 (December 2020) - Kahan, Joseph B.; Li, Don; Schneble, Christopher A.; Huang, Patrick; Bullock, James; Porrino, Jack; Medvecky, Michael J.
Background: A description of the precise locations of ligamentous and myotendinous injury patterns of acute posterolateral corner (PLC) injuries and their associated osseous and neurovascular injuries is lacking in the literature. Purpose: To characterize the ligamentous and myotendinous injury patterns and zones of injury that occur in acute PLC injuries and determine associated rates of peroneal nerve palsies and vascular injuries, as well as fracture and dislocation. Study Design: Case series; Level of evidence, 4. Methods: We retrospectively identified all patients treated for an acute multiligament knee injury (MLKI) at our level 1 trauma center from 2001 to 2018. From this cohort, all patients with PLC injuries were identified. Demographics, involved ligaments and tendons, neurovascular injury, and presence of fracture and dislocation were compared with the larger multiligament knee cohort. Incidence and location of injury of PLC structures—from proximal to midsubstance and distal injury—were recorded. Results: A total of 100 knees in 100 patients were identified as having MLKIs. A total of 74 patients (74%) had lateral-sided ligament injuries. Of these, 23 (31%) had a peroneal nerve palsy associated with their injury; 10 (14%), a vascular injury; and 23 (31%), a fracture. Patients with PLC injuries had higher rates of peroneal nerve injury as compared with those having acute MLKIs without a PLC injury (31% vs 4%; P = .005). Patients with a complete peroneal nerve palsy (n = 17) were less likely to regain function than those with a partial peroneal nerve palsy (n = 6; 12% vs 100%; P < .0001). Complete injury to the lateral collateral ligament (LCL) occurred in 71 of 74 (96%) PLC injuries, with 3 distinct patterns of injury demonstrated. Fibular avulsion of the LCL was the most common zone of injury (65%), followed by femoral avulsion (20%) and midsubstance tear (15%). Location of injury to the LCL was associated with the rate of peroneal nerve injury, with midsubstance tears and fibular avulsions associated with higher rates of peroneal nerve injury. Conclusion: MLKIs with involvement of the PLC are more likely to suffer peroneal nerve injury. The LCL is nearly always involved, and its location of injury is predictive of peroneal nerve injury. Patients with a complete peroneal nerve palsy at presentation are much less likely to regain function.